Primary bone diffuse large B-cell lymphoma: a retrospective evaluation on 76 cases from French institutional and LYSA studies. Issue 12 (1st December 2016) - Pilorge, Sylvain; Harel, Stephanie; Ribrag, Vincent; Larousserie, Frédérique; Willems, Lise; Franchi, Patricia; Legoff, Marielle; Biau, David; Anract, Philippe; Roux, Christian; Blanc-Autran, Estelle; Delarue, Richard; et al.
Abstract: Primary bone diffuse large B-cell lymphoma (PB-DLBCL) is a rare DLBCL location variant. We treated 76 PB-DLBCL patients by immuno-chemotherapy, resulting in an 84% sustained complete remission rate and a 78.9% survival over a 4.7-year median follow-up period. Ann Arbor stage IV and high age-adjusted international prognostic index were predictive of adverse outcome in univariate analysis. In multivariate analysis using a Cox model, only aa-IPI predicted long-term survival. While based on a limited number of cases, we suggested that radiotherapy may be useful as a consolidation modality in PB-DLBCL. We also suggested that positron emission tomography/CT scan should be interpreted with caution due to a persistent [18F]fluorodeoxyglucose [18FDG] uptake of bone lesions even after remission in some in PB-DLBCL patients. Our study based on a homogeneous cohort of PB-DLBCL patients confirmed the favorable outcome of this DLBCL variant and support the implementation of prospective clinical trials in this disease.